A Programming Environment for Visual Block-Based Domain-Specific Languages - Kurihara, Azusa; Sasaki, Akira; Wakita, Ken; Hosobe, Hiroshi (Procedia computer science, 2015)
Visual block-based programming is useful for various users such as novice programmers because it provides easy operations and improves the readability of programs. Also, in programming education, it is known to be effective to initially present basic language features and then gradually make more advanced features available. However, the cost of implementing such visual block-based languages remains a challenge. In this paper, we present a programming environment for providing visual block-based domain- specific languages (visual DSLs) that are translatable into various programming languages. In our environment, programs are built by combining visual blocks expressed in a natural language. Blocks represent program elements such as operations and variables. Tips represent snippets, and macro blocks represent procedures. Using Tips and macros make code more abstract, and reduce the number of blocks in code. Visual DSLs can be a front-end for various languages. It can be easily restricted and extended by adding and deleting blocks. We applied our programming environment to Processing, an educational programming language for media art. We show that the environment is useful for novice programmers who learn basic concepts of programming and the features of Processing.